EM-FOR: simple and low-cost force on a straight current-carrying conductor in a magnetic field experimental kit - Anis Nazihah Mat Daud (Tanjung Malim, 2023)
EM-FOR: simple and low-cost force on a straight current-carrying conductor in a magnetic field experimental kit by Anis Nazihah Mat Daud